The association between endocrine therapy use and dementia among post-menopausal women treated for early-stage breast cancer in Ontario, Canada. Issue 7 (September 2020) - Blanchette, Phillip S.; Lam, Melody; Le, Britney; Richard, Lucie; Shariff, Salimah Z.; Pritchard, Kathleen I.; Raphael, Jacques; Vandenberg, Ted; Fernandes, Ricardo; Desautels, Danielle; Chan, Kelvin K.W.; Earle, Craig C.
Abstract: Purpose: The association between endocrine therapy and risk of dementia remains uncertain. We investigated the association between adjuvant endocrine therapy for breast cancer and risk of developing dementia in a real-world, population-based study. Methods: We used health administrative data collected from post-menopausal women (aged ≥66 years) who were diagnosed with breast cancer and started on adjuvant endocrine therapy from 2005 to 2012 with follow-up until 2017. Patients were classified by the use of either an aromatase inhibitor or tamoxifen and followed to estimate the unadjusted cumulative incidence of developing dementia. A multivariable Cox proportional hazards model was created adjusting for age, income quintile, medical co-morbidities, and duration of endocrine therapy. Results: We identified 12, 077 patients of whom 73% were treated with an aromatase inhibitor and 27% with tamoxifen. Our multivariable analysis showed a lower rate of dementia in patients treated with an aromatase inhibitor as compared to tamoxifen [Hazard ratio (HR) = 0.88, 95% confidence interval (CI): 0.78–0.98, p -value = .02) at a median follow-up of 5.9 years. The 5-year dementia rate among patient treated with either an aromatase inhibitor or tamoxifen was 7.4% and 9.2% respectively. Older age, previous history of ischemic heart disease, diabetes, hypertension and history of stroke were all significantly associated with the development of dementia. Conclusion: Aromatase inhibitor therapy was associated with a decreased incidence of dementia as compared to treatment with tamoxifen among post-menopausal women with early stage breast cancer. Further prospective studies with longer-term follow-up investigating the neurocognitive effects of endocrine therapy are warranted.